The Oxford handbook of media, technology, and organization studies - Beyes, Timon, 1973-; Holt, Robin, 1966-; Pias, Claus, (Oxford handbooks online., 2020)
Our most basic relationship with the world is one of technological mediation. Nowadays our available tools are digital, and increasingly what counts in economic, social, and cultural life is what can be digitally stored, distributed, replayed, augmented, and switched. Yet the digital remains very much materially configured, and though it now permeates nearly all human life it has not eclipsed all older technologies. This handbook is grounded in an understanding that our technologically mediated condition is a condition of organization. It maps and theorizes the largely unchartered territory of media, technology, and organization studies. Written by scholars of organization and theorists of media and technology, the chapters focus on specific, and specifically mediating, objects that shape the practices, processes, and effects of organization.